ANALYSIS OF THE DEPICTION OF CRIME IN THE VIDEO GAME GRAND THEFT AUTO (GTA) V AS A POTENTIAL FOR CHILDREN’S LEARNING OF CRIME - Fakhri Usmita; Efendi, Alfi Sakri (Sisi Lain Realita, 2024)
This study examines the depiction of crime in the video game Grand Theft Auto V (GTA V) and its impact on criminal behavior in children and adolescents. GTA V allows players to engage in illegal actions, such as robbery and murder, without clear moral consequences. Exposure to such behavior may influence young players' perceptions of the normalization of criminal behavior, as they may struggle to differentiate between the fictional world and reality. This research aims to understand how the portrayal of crime in GTA V affects the views and behavior of young players. The methodology used is qualitative, involving interviews with players, parents, and psychologists. The findings indicate that while some players can distinguish between fiction and reality, repeated exposure to violence can alter their views on crime, making it seem appealing or even beneficial. The study concludes that GTA V has the potential to shape a mindset more familiar with violence and crime. Therefore, parental supervision and critical understanding of the content consumed are crucial in preventing negative impacts on the psychological and social development of children and adolescents.